High-corrosion-resistance slag microcrystalline glass prepared by microwave-electricity combined heating and preparation method of high-corrosion-resistance slag microcrystalline glass
Through microwave-electric combined heating technology, combining the advantages of microwave heating and electric heating, highly corrosion-resistant slag microcrystalline glass is prepared, which solves the problems of insufficient corrosion resistance and energy utilization efficiency in traditional methods, realizes efficient and energy-saving high-performance microcrystalline glass preparation, and promotes its application in the nuclear industry and marine engineering fields.
Patent Information
- Application Number
- CN202510978313.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-09-30
AI Technical Summary
Traditional preparation methods are insufficient in improving the corrosion resistance and energy efficiency of slag glass-ceramics, hindering its development and application in the industrial field.
Microwave-electric combined heating technology is used to improve the crystallization state through microwave heating technology. The fast, controllable and clean characteristics of microwave heating are combined with the precise temperature control of electric heating to prepare highly corrosion-resistant slag microcrystalline glass. Iron tailings, metallurgical slag and fly ash are used as raw materials to control the phase interface structure of diopside and spinel, achieving efficient regulation.
It significantly improves the corrosion resistance and mechanical properties of slag glass-ceramics, shortens the crystallization time, saves more than 75% of energy, reduces energy consumption, improves the corrosion resistance and mechanical strength of the material, and expands its application in the nuclear industry and marine engineering.
Smart Images

Figure CN120717692A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of highly corrosion-resistant slag glass-ceramics, and in particular to a method for preparing highly corrosion-resistant slag glass-ceramics by utilizing microwave-electricity combined heating. Background Art
[0002] Glass-ceramics are polycrystalline composite materials with fine, uniformly distributed grains, produced by controlled crystallization of a base glass of a specific composition at a specific temperature. Numerous types of glass-ceramics are currently produced worldwide, including heat-resistant, wear-resistant, corrosion-resistant, structural, piezoelectric, bio-ceramics, and architectural glass-ceramics. They have been widely promoted and applied in fields such as machinery, electronics and electrical engineering, aerospace, chemical corrosion protection, mining, road construction, construction, and medicine. Slag glass-ceramics, manufactured from industrial waste or mine tailings, not only boasts excellent performance, affordability, and a wide range of applications, but also plays a significant role in the utilization of "three wastes," the rational use of natural resources, comprehensive pollution control, and the development of a circular economy. Consequently, they are gaining increasing attention and are considered a promising new material for the 21st century.
[0003] There are currently several methods for preparing glass-ceramics:
[0004] (1) Glass-ceramics are obtained by melting (or cooling) a base glass and then heat-treating the base glass. This method is referred to as the base glass heat treatment method. It is easy to shape, the product is dense, there are many glass product shaping methods, the cost is low, and the glass has few defects. However, its disadvantages are energy consumption, long production cycle, difficulty in controlling the size distribution of the product, and high processing cost.
[0005] (2) Glass-ceramics are obtained by preparing a xerogel through the sol-gel method and then heat-treating the xerogel. This method is also called gel heat treatment. Homogeneity can reach the molecular level, and selective doping is possible. However, the disadvantages are high starting material costs, long post-heat treatment times, large shrinkage, and easy deformation.
[0006] (3) Glass-ceramics are prepared by mixing raw materials, pressing, drying, and then sintering. This method is referred to as the sintering method. The firing process is easy to control, the melting time is short, the processing cost is low, and the product precipitation is easy to control. The disadvantages are energy consumption, long production time, easy precipitation, many defects in the product, and poor optical properties.
[0007] (4) Polymer network gel method: Due to the hindrance of the polymer network, the chance of molecular contact and aggregation is reduced, which is conducive to the formation of nanopowders with less agglomeration. The raw material requirements are simple, the cost is low, and the synthesis speed is fast. The disadvantages are complex process, long heat treatment time, and large shrinkage.
[0008] (5) Products are obtained by float forming. After melting, rapid cooling, annealing, and certain heat treatments are performed to obtain uniform and transparent micro-glass products. The products are dense, have few defects, and can be mass-produced. The disadvantage is that the raw material composition requirements are high, the melting process system and the nucleation crystallization requirements are strict, and they are generally difficult to control.
[0009] With the rapid development of industry, the treatment and reuse of industrial waste has become an urgent environmental and resource issue. Against this backdrop, slag glass-ceramics has emerged as an important branch of glass-ceramics. With its unique advantages, such as high mechanical strength, excellent high-temperature resistance, wear resistance, and chemical stability, it has become a key approach to high-value utilization of industrial solid waste. However, traditional preparation methods have shortcomings in improving corrosion resistance and energy efficiency, seriously hindering its development and application.
[0010] For glass-ceramics, the way in which the crystals are precipitated cannot be ignored, as it can significantly alter the material's physical properties. Therefore, a new preparation method is urgently needed. Summary of the Invention
[0011] The present invention provides a method for preparing highly corrosion-resistant slag microcrystalline glass using microwave-electric combined heating, and utilizes microwave heating technology to improve its crystallization state. Microwave heating technology, as a new type of efficient and pollution-free energy source, has the advantages of fast heating, volume heating, high efficiency, controllability, cleanliness, and selective heating. It can improve energy utilization and realize material microstructure regulation.
[0012] A high-corrosion-resistant slag glass-ceramic prepared by microwave-electricity combined heating comprises 30-60% by mass of iron tailings, 30-50% by mass of metallurgical slag and 15-30% by mass of fly ash.
[0013] Preferably, the metallurgical slag of the present invention is one of blast furnace slag and stainless steel slag.
[0014] A method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electric combined heating comprises the following steps:
[0015] Step S1: taking a certain mass percentage of iron ore tailings, metallurgical slag, and fly ash and mixing them evenly;
[0016] Step S2: placing the raw material processed in step S1 in a muffle furnace for melt annealing;
[0017] Step S3: placing the glass annealed in step S2 in a microwave oven for nucleation and crystallization heat treatment to obtain microcrystalline glass.
[0018] Preferably, in step S2 of the present invention, the melting temperature is 1400-1500° C. and the melting time is 3-4 hours.
[0019] Preferably, in step S2 of the present invention, the annealing temperature is 500-650° C. and the time is 1-2 hours.
[0020] Preferably, in step S3 of the present invention, during the microwave nucleation and crystallization heat treatment, the nucleation temperature is 660-740° C., and the holding time is 0.5-1 hour.
[0021] Preferably, in step S3 of the present invention, during the microwave nucleation and crystallization heat treatment, the crystallization temperature is 760-880° C., and the crystallization time is 0.5-1 hour.
[0022] Preferably, in step S3 of the present invention, during the microwave nucleation and crystallization heat treatment, the auxiliary heating medium is silicon carbide, activated carbon, or graphite.
[0023] The present invention aims to improve the performance and industrial applicability of tailings glass-ceramics. In traditional preparation, it is extremely challenging to precisely control the crystal phase, glass phase and phase interface structure to achieve high corrosion resistance and synergistic enhancement of mechanical properties. The present invention combines microwave-electric combined heat treatment to control the complex phase structure and promote its application in the fields of nuclear industry, marine engineering, etc. At the same time, compared with traditional methods, this method can shorten the crystallization time to 1 / 6, save more than 75% of energy, significantly reduce the absorption of microwave energy by iron and chromium components, promote spinel phase separation and diopside growth, thereby efficiently preparing highly corrosion-resistant and high-performance slag glass-ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic flow chart of the preparation method of the present invention.
[0025] Figure 2 It is a schematic diagram of X-ray diffraction (XRD) data of glass-ceramics in different states.
[0026] Figure 3 It is the energy spectrum and Raman map data of the heterogeneous phase in microcrystalline glass.
[0027] Figure 4 This is a schematic diagram of the simulation calculation of the compressive deformation of the diopside lattice induced by spinel. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described in detail below with reference to the embodiments and drawings:
[0029] A method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electricity combined heating comprises 30-60% by mass of iron ore tailings, 30-50% by mass of metallurgical slag, and 15-30% by mass of fly ash. The metallurgical slag is one of blast furnace slag and stainless steel slag.
[0030] Combine Figure 1A method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electric combined heating comprises the following steps:
[0031] Step S1: taking a certain mass percentage of iron tailings, metallurgical slag and fly ash to mix and batch the ingredients, wherein the sum of the components after mixing is 100%, and the prepared raw materials are mixed evenly.
[0032] Step S2: placing the raw materials processed in step S1 in a muffle furnace for melt annealing.
[0033] The heat treatment system is as follows: melting temperature: 1400-1500°C, time: 3-4 hours; annealing temperature: 500-650°C, time: 1-2 hours.
[0034] Step S3: placing the glass annealed in step S2 in a microwave oven for nucleation and crystallization heat treatment to obtain microcrystalline glass.
[0035] The microwave oven nucleation crystallization heat treatment system is as follows: nucleation temperature 660-740°C, holding time: 0.5-1 hour; crystallization temperature 760-880°C, 0.5-1 hour; auxiliary heating medium: silicon carbide, activated carbon, graphite.
[0036] After going through the above process, a microcrystalline glass product is obtained. Diopside is the main crystal phase in the microcrystalline glass, and spinel is induced to precipitate through Fe2O3 to form a wrapping structure to improve corrosion resistance.
[0037] In addition, spinel induces diopside to form a special epitaxial relationship. That is, the spinel (111) crystal plane epitaxies the diopside (200) crystal plane, and the crystal band axis parallel relationship is that the spinel
[112] crystal phase is parallel to the diopside
[001] crystal phase. This special encapsulation relationship not only fills the diopside grain boundary voids, but also blocks the penetration path of the corrosive medium, achieving a synergistic enhancement of corrosion resistance. At the same time, the diopside lattice undergoes compression deformation, making the crystal structure more dense. This further improves its mechanical and corrosion resistance properties.
[0038] Example 1
[0039] Iron tailings, blast furnace slag and fly ash are used as raw materials, with the weight percentage of iron tailings being 30%, the weight percentage of blast furnace slag being 50%, and the amount of fly ash added being 20%. The above raw materials are weighed, mixed evenly and then loaded into a crucible. The crucible filled with raw materials is placed in a muffle furnace at 1400℃ and kept warm for 4 hours to make the molten glass clear and uniform. The molten glass is placed in a muffle furnace at 600℃ for annealing to eliminate internal stress. The annealed glass is first subjected to a nucleation treatment in a microwave oven at 660℃ for 1 hour, and then the microwave oven is heated to 830℃ for 1 hour for crystallization treatment to finally obtain a microcrystalline glass sample.
[0040] When microwave- and conventionally prepared glass-ceramics were immersed in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss was only 0.05% (compared to 0.63% for the conventional method). The compressive strength of the microwave-electric combined process sample reached 185 MPa, while the conventional electric heating process sample reached 155 MPa.
[0041] Example 2
[0042] Iron tailings, blast furnace slag and fly ash are used as raw materials, with the weight percentage of iron tailings being 60%, the weight percentage of blast furnace slag being 25%, and the amount of fly ash added being 15%. The above raw materials are weighed, mixed evenly and then loaded into a crucible. The crucible filled with raw materials is placed in a muffle furnace at 1500℃ and kept warm for 3 hours to make the molten glass clear and uniform. The molten glass is placed in a muffle furnace at 500℃ for annealing to eliminate internal stress. The annealed glass is first subjected to a nucleation treatment in a microwave oven at 740℃ for 0.5 hours, and then the microwave oven is heated to 880℃ for 0.5 hours for crystallization treatment to finally obtain a microcrystalline glass sample.
[0043] When microwave-generated glass-ceramics and conventionally prepared glass-ceramics were immersed in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss was only 0.08% (compared to 0.75% for the conventional method). The compressive strength of the microwave-electric combined process sample reached 192 MPa, while the conventional electric heating process sample reached 151 MPa.
[0044] Example 3
[0045] Iron tailings, blast furnace slag and fly ash are used as raw materials, with the weight percentage of iron tailings being 50%, the weight percentage of blast furnace slag being 25%, and the amount of fly ash added being 25%. The above raw materials are weighed, mixed evenly and then loaded into a crucible. The crucible filled with raw materials is placed in a muffle furnace at 1500℃ and kept warm for 3 hours to make the molten glass clear and uniform. The molten glass is placed in a muffle furnace at 500℃ for annealing to eliminate internal stress. The annealed glass is first subjected to a nucleation treatment in a microwave oven at 730℃ for 0.5 hours, and then the microwave oven is heated to 880℃ for 0.5 hours for crystallization treatment to finally obtain a microcrystalline glass sample.
[0046] When microwave-generated glass-ceramics and conventionally prepared glass-ceramics were immersed in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss was only 0.07% (compared to 0.65% for conventional methods). The compressive strength of the microwave-electrically heated sample reached 188 MPa, while that of the conventionally heated sample reached 156 MPa.
[0047] Example 4
[0048] Iron tailings, blast furnace slag and fly ash are used as raw materials, with the weight percentage of iron tailings being 60%, the weight percentage of blast furnace slag being 25%, and the amount of fly ash added being 15%. The above raw materials are weighed, mixed evenly and then loaded into a crucible. The crucible filled with raw materials is placed in a muffle furnace at 1500℃ and kept warm for 3 hours to make the molten glass clear and uniform. The molten glass is placed in a muffle furnace at 500℃ for annealing to eliminate internal stress. The annealed glass is first subjected to a nucleation treatment in a microwave oven at 720℃ for 0.5 hours, and then the microwave oven is heated to 820℃ for 0.5 hours for crystallization treatment to finally obtain a microcrystalline glass sample.
[0049] When microwave-generated glass-ceramics and conventionally prepared glass-ceramics were immersed in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss was only 0.06% (compared to 0.72% for the conventional method). The compressive strength of the microwave-electric combined process sample reached 192 MPa, while the conventional electric heating process sample reached 155 MPa.
[0050] Example 5
[0051] Iron tailings, blast furnace slag and fly ash are used as raw materials, with the weight percentage of iron tailings being 40%, the weight percentage of blast furnace slag being 30%, and the amount of fly ash added being 30%. The above raw materials are weighed, mixed evenly and then loaded into a crucible. The crucible filled with raw materials is placed in a muffle furnace at 1400℃ and kept warm for 4 hours to make the molten glass clear and uniform. The molten glass is placed in a muffle furnace at 650℃ for annealing to eliminate internal stress. The annealed glass is first subjected to a nucleation treatment in a microwave oven at 660℃ for 1 hour, and then the microwave oven is heated to 760℃ for 0.5 hour for crystallization treatment to finally obtain a microcrystalline glass sample.
[0052] When microwave- and conventionally prepared glass-ceramics were immersed in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss was only 0.08% (compared to 0.52% for the conventional method). The compressive strength of the microwave-electric combined process sample reached 190 MPa, while the conventional electric heating process sample reached 150 MPa.
[0053] Figure 2Schematic diagram of X-ray diffraction (XRD) data for glass-ceramics under different conditions. Obs represents experimentally measured XRD data for the glass-ceramics, Calc represents Rietveld-refined XRD data, Diff represents the error between the experimental and refined data, BKG represents the baseline for the XRD data, Diopside designates the position of the characteristic XRD peak for diopside, and CaF2 designates the position of the characteristic XRD peak for calcium fluoride. Quantitative analysis of the phase distribution in the glass-ceramics using XRD refinement using 20 wt.% calcium fluoride and 80 wt.% diopside.
[0054] from Figure 2 It can be seen that the main crystal phase in the microcrystalline glass is diopside phase, and the structure of diopside is ((Mg 0.9 Fe 0.06 Al 0.02 Cr 0.02 )(Ca 0.85 Na 0.01 Mg 0.08 Fe 0.06 )(Si 1.95 Al 0.05 )O6. Its lattice is a=9.692b=8.874c=5.2651beta=106.172, and the diopside phase content is 29wt.%.
[0055] Figure 3 Figure 1 shows the EDS and Raman spectra of a heterogeneous phase in glass-ceramics, demonstrating the structure and composition of the second component analyzed using EDS and Raman spectroscopy. (a) is a SEM image of the heterogeneous phase in the glass (white point 1 represents the heterogeneous phase, gray point 2 represents the glass substrate). The images to the right of (a) are, from left to right, the following: SEM EDS image, oxygen distribution; SEM EDS image, calcium distribution; SEM EDS image, chromium distribution; and the following: SEM EDS image, magnesium distribution; SEM EDS image, aluminum distribution; SEM EDS image, silicon distribution. (b) is a point scan of the heterogeneous phase, corresponding to point 1 in (a). (c) is a point scan of the glass substrate, corresponding to point 2 in (a). (d) is the experimentally measured Raman spectrum of the heterogeneous phase. Figure (e) shows a standard Raman spectrum of spinel. Based on the Raman spectrum and the energy spectrum results, it can be determined that the heterogeneous phase is a magnesium-aluminum-chromium spinel phase.
[0056] Combine Figure 4The spinel-induced diopside lattice was subjected to compression deformation simulation (1% compression deformation), which made the crystal structure more compact. Monte Carlo calculations showed that the (200) crystal plane of the material had a reduced ability to bind H ions in the acid solution after compression. The minimum energy before compression was -0.94044286 eV, while the minimum energy after compression was -0.71338683 eV.
[0057] This invention achieves energy-saving, high-efficiency, and high-performance production of highly corrosion-resistant slag glass-ceramics through the innovative combination of microwave-electric combined heat treatment technology and the synergistic utilization of diverse industrial solid wastes. Compared with existing technologies, its core advantages are reflected in the following aspects:
[0058] 1. Energy saving and efficiency improvement
[0059] Energy consumption is reduced by over 75%. Traditional heat treatment processes require 3-4 hours of heat preservation at 1400-1500°C. However, the microwave-electric combined technology combines selective microwave heating (elements like iron and chromium preferentially absorb microwave energy) with precise temperature control by electric heating to shorten the crystallization holding time to 0.5-1 hour, with total energy consumption reduced to only 25% of the traditional process. Rapid crystallization: The microwave field accelerates ion migration and crystal nucleation. The synergistic effect of spinel-induced diopside growth increases the crystallization rate by 6 times, significantly shortening the production cycle.
[0060] 2. Breakthrough in corrosion resistance
[0061] Wide pH adaptability: By regulating the synergistic structure of diopside (CaMgSi2O6) and spinel (MgAl2O4 / FeCr2O4), the material's mass loss rate in both strong acid (pH = 1) and strong alkaline (pH = 14) environments is less than 0.1%, surpassing traditional slag glass-ceramics (mass loss rate > 0.5%). Enhanced impermeability: Spinel fills the diopside grain boundary voids, forming a dense network structure, reducing the penetration depth of corrosive media from 50-100μm in traditional processes to below 10μm.
[0062] 3. Optimization of mechanical properties
[0063] High Strength and Wear Resistance: The diopside-spinel composite structure enables the material to achieve a flexural strength of 220-250 MPa and a compressive strength exceeding 1200 MPa, representing a 40% increase over traditional slag glass-ceramics (flexural strength of 150-180 MPa). Excellent Thermal Shock Resistance: The thermal expansion coefficients of the crystalline and glass phases match, allowing the material to withstand rapid cooling cycles from 1000°C to room temperature without cracking, making it suitable for high-temperature corrosive environments (such as chemical reactor linings).
[0064] 4. Environmental protection and resource utilization advantages
[0065] Solid waste utilization rate>85%: The raw materials are mainly iron tailings (30-60%), metallurgical slag (30-50%), and fly ash (15-30%), realizing high-value utilization of industrial solid waste and reducing storage pollution. Heavy metal solidification rate>99%: Microwave field promotes Cr 3+ 、Fe 3+ Heavy metal ions such as iodine enter the spinel lattice, and the leaching toxicity (TCLP test) is far lower than the national standard (GB5085.3-2007).
[0066] 5. Process controllability and universality
[0067] Precise microstructure control: Microwave fields regulate crystal nucleation and growth direction, while electric heating achieves ±5°C temperature control accuracy, enabling targeted optimization of the diopside / spinel ratio (e.g., 60-80% diopside and 20-40% spinel). Wide adaptability to raw materials: The formula is compatible with a variety of industrial solid wastes containing iron, chromium, calcium, and magnesium (e.g., stainless steel slag, copper slag, and red mud), and is adaptable to different raw material systems through fine-tuning of the composition (SiO2 / Al2O3 = 4-6:1, CaO / MgO = 1.2-1.5:1).
[0068] 6. Significant economic benefits
[0069] 30% Cost Reduction: Microwave-electricity combined technology reduces energy consumption and time costs, and eliminates the need for the addition of precious metal nucleating agents (traditional processes require the addition of ZrO2, Pt, etc.). Expanded Application Scenarios: The product can replace high-cost corrosion-resistant alloys (such as Hastelloy) and ceramic materials, offering significant cost-effectiveness in nuclear waste packaging, marine corrosion protection projects, and chemical reactors.
[0070] Acid resistance test: After immersion in a 20% H2SO4 solution at 70°C for 24 hours, the mass loss rate was only 0.08% (compared to 0.52% for the traditional process). Compressive strength: The microwave-electric combined process sample reached 190MPa, while the traditional electric heating process sample reached 150MPa. Energy consumption comparison: To produce one ton of microcrystalline glass, the traditional process consumes 1800kWh of electricity, while the present invention only requires 420kWh.
[0071] The present invention breaks through the technical bottlenecks of slag microcrystalline glass in corrosion resistance, mechanical properties and energy consumption through microwave-electric combined heat treatment technology and complex phase grain boundary structure design, providing an innovative solution for the resource utilization of industrial solid waste and the development of high-end corrosion-resistant materials.
Claims
1. A method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electric combined heating, characterized in that The invention comprises 30-60% by mass of iron tailings, 30-50% by mass of metallurgical slag and 15-30% by mass of fly ash.
2. The method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electric combined heating according to claim 1, characterized in that Metallurgical slag is either blast furnace slag or stainless steel slag.
3. A method for preparing highly corrosion-resistant slag glass-ceramics by microwave-electric combined heating according to claim 1 or 2, characterized in that The steps include: Step S1: taking a certain mass percentage of iron ore tailings, metallurgical slag, and fly ash and mixing them evenly; Step S2: placing the raw material processed in step S1 in a muffle furnace for melt annealing; Step S3: placing the glass annealed in step S2 in a microwave oven for nucleation and crystallization heat treatment to obtain microcrystalline glass.
4. The preparation method according to claim 3, wherein: In step S2, the melting temperature is 1400-1500° C. and the melting time is 3-4 hours.
5. The preparation method according to claim 3, wherein: In step S2, the annealing temperature is 500-650° C. and the time is 1-2 hours.
6. The preparation method according to claim 3, wherein: In step S3, during the microwave nucleation and crystallization heat treatment, the nucleation temperature is 660-740° C. and the holding time is 0.5-1 hour.
7. The preparation method according to claim 3, wherein: In step S3, during the microwave nucleation and crystallization heat treatment, the crystallization temperature is 760-880° C. and the crystallization time is 0.5-1 hour.
8. The preparation method according to claim 3, wherein: In step S3, during the microwave nucleation and crystallization heat treatment, the auxiliary heating medium is silicon carbide, activated carbon, or graphite.
